Systematic evaluation of retroviral LTRs as cis-regulatory elements in mouse embryos - Jian Yang; Lauryn Cook; Zhiyuan Chen (Cell Reports, 2024)
Summary: In mammals, many retrotransposons are de-repressed during zygotic genome activation (ZGA). However, their functions in early development remain elusive largely due to the challenge to simultaneously manipulate thousands of retrotransposon insertions in embryos. Here, we applied CRISPR interference (CRISPRi) to perturb the long terminal repeat (LTR) MT2_Mm, a well-known ZGA and totipotency marker that exists in ∼2,667 insertions throughout the mouse genome. CRISPRi robustly perturbed 2,485 (∼93%) MT2_Mm insertions and 1,090 (∼55%) insertions of the closely related MT2C_Mm in 2-cell embryos. Remarkably, such perturbation caused downregulation of hundreds of ZGA genes and embryonic arrest mostly at the morula stage. Mechanistically, MT2 LTRs are globally enriched for open chromatin and H3K27ac and function as promoters/enhancers downstream of OBOX/DUX proteins. Thus, we not only provide direct evidence to support the functional importance of MT2 activation in development but also systematically define cis-regulatory function of MT2 in embryos by integrating functional perturbation and multi-omic analyses.